First-Principles Modeling of Electron-Phonon Scattering Rates in Hydrogenated Graphene - V. N. Mishchanka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2025)
Graphene, a representative of a new generation of 2D materials, remains in the center of scientific research as a reflection of its unique electrical and mechanical properties. The article presents the results of a study of electron scattering procedures of optical and acoustic phonons in graphene modified with hydrogen atoms, a C2H2 structure known as graphane. The obtained dependences of the scattering rates take into account the combined processes of phonon emission and absorption by electrons, but the interaction of phonons with the substrate material is not considered. The scattering rates play an important role in a detailed study of the dynamics of charge carrier transport in semiconductor structures containing heterogeneous layers. Their use makes it possible to implement the well-known many-particle Monte Carlo method, widely used in modeling complex semiconductor devices. The obtained results will allow us to study new heterostructured devices based on graphene and its modifications with improved output characteristics in high-frequency operating ranges.